Phytoremediation and long-term metal uptake monitoring of silver, selenium, antimony, and thallium by black pine (Pinus nigra Arnold) - Sevik, Hakan; Yildiz, Yafes; Özel, Halil Barıs (BioResources, 2024)
The usability of black pine (Pinus nigra Arnold) in both monitoring the changes in the concentrations of silver (Ag), selenium (Se), antimony (Sb), and thallium (Tl), and in reducing soil or air pollution was investigated. In the study, annual rings of a Pinus nigra tree, cut in 2023 and identified as 356 years old, were grouped into 10-year intervals, and then the changes in these heavy metals throughout the process were determined by analysing the concentrations of these elements. Additionally, the relationship of these elements with other elements was also detected in the scope of the study. The study results suggested that Pinus nigra was not a suitable bio-monitor for monitoring the changes in Ag, Se, Sb, and Tl concentrations in the soil or air, but it was a highly suitable species for phytoremediation studies aimed at reducing the pollution of these elements. Moreover, it was determined that the relationships of the studied elements with essential nutrients, such as Mg, Ca, P, K, Al, Zn, Ni, and Fe, were not statistically significant and were very weak; whereas they exhibited positive and very strong relationships with elements known to be highly harmful for health such as V, Pb, and As.
Keywords: 13. Climate action; 15. Life on land